THE CONCEPT OF GUILT IN CRIMINAL LAW - Dadabaeva Nilufar Farkhodovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article analyzes views on understanding the nature of guilt in criminal law. The content of psychological and normative concepts of guilt was tried to reveal. A proposal to define the concept of guilt has been put forward in criminal law.